Performance of Removal Efficiency in the Main Wastewater Treatment Plant for Physical, Chemical (Fe, Zn, Bod), and Biological Parameters at the Steam Power Plant (Pltu) Paiton Units 3, 7 & 8 - Totok Widianto; Zainal Arifin; Erwan Yulianto (Journal La Multiapp, 2026)
Wastewater treatment in Wastewater Treatment Plant (WWTP) plays a vital role in protecting environmental quality. This study aims to evaluate the treatment efficiency of various pollutant parameters such as Total Suspended Solids (TSS), Iron (Fe), Zinc (Zn), Biochemical Oxygen Demand (BOD), and Total Coliform, based on data collected during the period 2023-2024. The results of the analysis showed fluctuations in pollutant levels in the influent and effluent of WWTP, with TSS removal efficiency reaching 95.83% in August 2023, and Total Coliform showing the highest efficiency of 99.88% in the same month. Although most parameters showed significant reductions, there were months where the removal efficiency decreased, even showing negative values. These findings indicate anomalies in the treatment process that need to be addressed, especially in certain parameters. The analysis of variance (ANOVA) conducted showed no significant difference between pollutant levels, indicating consistency in the treatment results carried out by the WWTP. The importance of regular monitoring and evaluation of the wastewater treatment system to ensure that the wastewater from the WWTP process that is discharged does not pollute the environment. Efforts to improve treatment technology and implement better waste management practices are needed to achieve environmental sustainability effectively.